Hubungan program keluarga harapan (PKH) dengan tingkat kemiskinan di daerah tertinggal dan non tertinggal di Indonesia - Bejo Waluyo; Khoirunurrofik Khoirunurrofik (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2021)
Conditional cash transfer (CCT),known as the Program Keluarga Harapan (PKH), is a social assistance instrumentto reduce poverty in Indonesia. Therefore, this study examines the relationship of PKH in reducing the poverty rate in Indonesia andthe differences in its effects on less-developed and developed regions. This study uses panel data from 512 districts/cities in 2015-2019 with the fixed-effect model (FEM) estimation. The results show that PKH has a negative and significant relationship to the poverty rate in Indonesia, both in less-developed and developed regions, where its effect in reducing poverty rates is smaller in less-developed regions than in developed regions. It can happen because conditions in less-developed regions generally have a higher poverty gap, difficult regional accessibility, fairly high exclusion and inclusion error factors, and relatively limited basic education facilities compared to developed regions.